Atlas of human anatomy - Netter, Frank H. (Frank Henry), 1906-1991 (Philadelphia, PA : Elsevier, 2018)
"The only anatomy atlas illustrated by physicians, Atlas of Human Anatomy, 7th edition, brings you world-renowned, exquisitely clear views of the human body with a clinical perspective. In addition to the famous work of Dr. Frank Netter, you'll also find nearly 100 paintings by Dr. Carlos A. G. Machado, one of today's foremost medical illustrators. Together, these two uniquely talented physician-artists highlight the most clinically relevant views of the human body. In addition, more than 50 carefully selected radiologic images help bridge illustrated anatomy to living anatomy as seen in everyday practice." -- publisher's website.
Sect. 1: Introduction -- Introduction -- Electronic bonus plates -- Sect. 2: Head and neck -- Surface anatomy -- Superficial head and neck -- Bones and ligaments -- Neck -- Nasal region -- Oral region -- Pharynx -- Thyroid gland and larynx -- Orbit and contents -- Ear -- Meninges and brain -- Cranial and cervical nerves -- Cerebral vasculature -- Regional imaging -- Structures with high clinical significance -- Muscle tables -- Electronic bonus plates -- Sect. 3: Back and spinal cord -- Surface anatomy -- Bones and ligaments -- Spinal cord -- Muscles and nerves -- Cross-sectional anatomy -- Structures with high clinical significance -- Muscle tables -- Electronic bonus plates -- Sect. 4: Thorax -- Surface anatomy -- Mammary gland -- Body wall -- Lungs -- Heart -- Mediastinum -- Regional scans -- Cross-sectional anatomy -- Structures with high clinical significance -- Muscle table -- Electronic bonus plates -- Sect. 5: Abdomen -- Surface anatomy -- Body wall -- Peritoneal cavity -- Viscera (gut) -- Viscera (accessory organs) -- Visceral vasculature -- Innervation -- Kidneys and suprarenal glands -- Lymphatics -- Regional scans -- Cross-sectional anatomy -- Structures with high clinical significance -- Muscle table -- Electronic bonus plates -- Sect. 6: Pelvis and perineum -- Surface anatomy -- Bones and ligaments -- Pelvic floor and contents -- Urinary bladder -- Uterus, vagina, and supporting structures -- Perineum and external genitalia: female -- Perineum and external genitalia: male -- Homologues of genitalia -- Testis, epididymis, and ductus deferens -- Rectum -- Regional scan -- Vasculature -- Innervation -- Cross-sectional anatomy -- Structures and high clinical significance -- Muscle tables -- Electronic bonus plates -- Sect. 7: Upper limb -- Surface anatomy -- Cutaneous anatomy -- Shoulder and axilla -- Arm -- Elbow and forearm -- Wrist and hand -- Neurovasculature -- Regional imaging -- Structures with high clinical significance -- Muscle tables -- Electronic bonus plates -- Sect. 8: Lower limb -- Surface anatomy -- Cutaneous anatomy -- Hip and thigh -- Knee -- Leg -- Ankle and foot -- Neurovasculature -- Regional imaging -- Structures with high clinical significance -- Muscle tables -- Electronic bonus plates.
Includes index.
Keywords: Anatomi; Anatomy; Anatomi; Bildatlas; Anatomy; Picture atlas